Germination of Lolium perenne and Medicago Species under the Conditions of Drought and Silicon Application as Well as Variable pH and Medicago sativa Root Extracts - Barbara Borawska-Jarmułowicz; Grażyna Mastalerczuk (Plants, 2023)
Drought and allelopathic conditions impact the germination of seeds of grass and legume species used in mixtures on grassland. This study evaluated the effects of drought and Medicago sativa root extracts at different pH levels on the germination and characteristics of seedlings of Lolium perenne and selected Medicago species. Two experiments were carried out: the first explored the effects of drought induced by PEG solutions (0.0, −0.3, and −0.6 MPa) under silicon (Si) application; the second studied the influence of Medicago sativa root extracts (12 and 24 g/100 mL H2O) and variable pH solutions (control, 5.0, and 6.5) on seed germination. Germination was carried out on Petri dishes for individual species and in two-species mixtures. The drought conditions did not affect the germination capacity of seeds, but it increased the dry weight of the seedlings of the tested species. The application of silicon decreased the root length of the seedlings of all species, independent of the germination conditions. The higher concentration of M. sativa root extract combined with the studied pH solutions had an inhibitive impact on the germination capacity of L. perenne. Our findings revealed that the lower concentration of M. sativa root extract had a beneficial effect on the morphological features (length of roots and leaves, fresh and dry weight) of the seedlings when germination was carried out separately for both species. In the mixture, the effect was especially marked for L. perenne (only in terms of the root length and fresh weight of seedlings). The applied root extracts in combination with the acidic pH conditions limited the germination capacity and growth of the seedlings of L. perenne the most when germination was performed separately. It was concluded from this study that silicon application did not improve the germination capacity of seeds under drought conditions, whereas the germination of L. perenne seeds in a mixture with M. sativa mitigated the negative allelopathic effects of M. sativa root extracts on the seed germination capacity and morphological features of seedlings of L. perenne.